Proceedings 2018 Network and Distributed System Security Symposium 2018
DOI: 10.14722/ndss.2018.23318
|View full text |Cite
|
Sign up to set email alerts
|

Back To The Epilogue: Evading Control Flow Guard via Unaligned Targets

Abstract: In this paper, we show a significant design vulnerability in Windows CFG and propose a specific attack to exploit it: the Back to The Epilogue (BATE) attack. We show that with BATE an attacker can completely evade from CFG and transfer control to any location, thus obtaining arbitrary code execution. BATE leverages the tradeoff of CFG between precision, performance, and backwards compatibility; in particular, the latter one motivates 16-byte address granularity in some circumstances. This vulnerability, inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…A main design goal of our architecture is the ability to support the encoding of arbitrary code sequences. While previous research has shown that even in the presence of advanced ROP defenses it is possible to build realistic and Turing-complete gadget sets [6], one missing element in the research landscape is a publicly available, working ROP compiler that meets the needs of real-world attackers, for which building ROP chains remains predominantly a manual task [2,13]. Conversely, in recent years we have witnessed an increase in the complexity of ROP chains, which moved from being short simple sequences that bypass DEP to inject some shellcode, to very complex behaviors encoded entirely as ROP code [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A main design goal of our architecture is the ability to support the encoding of arbitrary code sequences. While previous research has shown that even in the presence of advanced ROP defenses it is possible to build realistic and Turing-complete gadget sets [6], one missing element in the research landscape is a publicly available, working ROP compiler that meets the needs of real-world attackers, for which building ROP chains remains predominantly a manual task [2,13]. Conversely, in recent years we have witnessed an increase in the complexity of ROP chains, which moved from being short simple sequences that bypass DEP to inject some shellcode, to very complex behaviors encoded entirely as ROP code [18].…”
Section: Discussionmentioning
confidence: 99%
“…Albeit CallerCheck and SymExec pose severe constraints to exploit writers 6 , they may easily be bypassed when the attacker is free to craft ROP gadgets within an application. Since our approach Figure 2: A possible implementation of the online patching mechanism performed by the detonator to make the ROP chain work in the presence of ASLR.…”
Section: Design Choicesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was deployed as an effective security technique to defend against memory corruption attacks; however, Control Flow Guard fails to protect against indirect jumps. Moreover, it is fully by-passable by Back To The Epilogue (BATE) attack [74]. BATE can corrupt the control-flow and direct it to an undefined location.…”
Section: Software-based Cfimentioning
confidence: 99%